The top 100 most cited articles in acne vulgaris: a bibliometric analysis - Sapir Itzhaki Gabay; Barak Zlakishvili; Yuliya Valdman-Grinshpoun; Amir Horev (PAGEPress Publications, 2024)
Background. A substantial body of literature has been published on acne vulgaris (AV) in the past five decades. Bibliometric analysis (BA) is a scientific, statistical evaluation review of published articles, providing a quantitative assessment of past research. Methods. The Web of Science (webOS) citation indexing database was used on 11 June 2023 to identify the top 100 cited articles on AV. Articles were listed in descending order by their annual citation (AC). Data sets were then subdivided into senior author, year and age of publication, journal and its impact factor, the number of total citations according to the webOS, corresponding and senior author's affiliated institution, country of origin, manuscript type, study design, and research focus. Results. The top 100 most cited articles were published between 1974 and 2020. The mean number of citations ranges between 82 and 688. The most cited paper was Guidelines of care for the management of Acne Vulgaris by Zaenglein, with an AC of 98.2. The largest number of manuscripts was published between 2001 and 2010 (n = 47). The British Journal of Dermatology had the highest number of published manuscripts (15). Of the original research papers, 28% were of a level of evidence 1, 56% focused on treatment, 19.5% on epidemiology, and 16.5% on pathogenesis. Conclusions. This analysis provides detailed bibliometric characteristics, highlighting the worldwide acne burden, with the hope that future researchers will explore the gaps in the AV literature.